2016
DOI: 10.1098/rsos.160576
|View full text |Cite
|
Sign up to set email alerts
|

Chemical communication is not sufficient to explain reproductive inhibition in the bumblebee Bombus impatiens

Abstract: Reproductive division of labour is a hallmark of eusociality, but disentangling the underlying proximate mechanisms can be challenging. In bumblebees, workers isolated from the queen can activate their ovaries and lay haploid, male eggs. We investigated if volatile, contact, visual or behavioural cues produced by the queen or brood mediate reproductive dominance in Bombus impatiens. Exposure to queen-produced volatiles, brood-produced volatiles and direct contact with pupae did not reduce worker ovary activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 46 publications
(86 reference statements)
1
46
0
Order By: Relevance
“…Beside this, it was shown that behavioral interactions of the queens, e.g., aggressive behavior towards workers, is necessary to induce sterility in workers in some primitively eusocial insect species, whereas chemical signals are not sufficient to affect worker's reproductive physiology [52][53][54][55][56][57]. Regarding our recent study on L. malachurum, we could clearly demonstrate that macrocyclic lactones as a chemical signal of the queen are solely sufficient to induce sterility in workers [20].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Beside this, it was shown that behavioral interactions of the queens, e.g., aggressive behavior towards workers, is necessary to induce sterility in workers in some primitively eusocial insect species, whereas chemical signals are not sufficient to affect worker's reproductive physiology [52][53][54][55][56][57]. Regarding our recent study on L. malachurum, we could clearly demonstrate that macrocyclic lactones as a chemical signal of the queen are solely sufficient to induce sterility in workers [20].…”
Section: Discussionmentioning
confidence: 61%
“…However, our recent comparative study on caste differences in cuticular chemical profiles among several halictid bee species with various social levels demonstrated, that castes of facultative eusocial species are chemically less distinct than castes in obligate eusocial species [21]. These smaller caste differences could be a hint for other signals to be involved in the regulation of worker's reproduction, potentially also aggressive behavior as was shown in other primitively eusocial species such as Polistes wasps and bumble bees [52][53][54][55][56][57]. However, more bioassays are needed to prove, if and how other than chemical signals play a role in regulating worker's reproduction in different halictid bee species.…”
Section: Discussionmentioning
confidence: 92%
“…This suggests that different components of the endocrine networks influencing reproductive physiology were independently modified during social evolution. Also, nutrition and cues from the social environment are some of the most important factors in reproductive suppression of workers among social bees (Amsalem et al, 2013;Kapheim et al, 2016;Lawson et al, 2016;Padilla et al, 2016), but these factors did not have a significant influence on variation in reproductive activation in solitary alkali bees. This suggests that changes in how nutrient-sensing and environment-sensing pathways regulate reproductive physiology were especially important in the evolutionary origins of reproductive castes.…”
Section: Discussionmentioning
confidence: 91%
“…Conversely, highly eusocial insects have evolved sophisticated forms of social communication. Within colonies of honey bees, bumble bees and sweat bees, behavior and reproductive physiology are dynamically regulated by the behavior and/or pheromones of nest-mates (Alaux et al, 2009;Amsalem and Hefetz, 2010;Arneson and Wcislo, 2003;Grozinger et al, 2003;Huang et al, 1998;Kapheim et al, 2016;Le Conte et al, 2001;Li-Byarlay et al, 2014;Padilla et al, 2016;Smith et al, 2009). Research with a facultatively eusocial halictid bee, M. genalis, suggests that aggression from older, reproductive females can limit reproductive development via JH suppression in newly emerged females (Kapheim et al, 2016;Smith et al, 2009Smith et al, , 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation